Delamination in cross-ply laminates: Identification of traction–separation relations and cohesive zone modeling. (23rd November 2015) - Farmand-Ashtiani, E.; Alanis, D.; Cugnoni, J.; Botsis, J.
Abstract: Identification of traction–separation relations is at the forefront of damage and fracture mechanics of composite laminates. Such relations are of particular interest in fracture of laminates consisting of layers of different fiber orientations. In this study, an iterative method based on internal strain measurements and parametric numerical modeling is employed to identify a traction–separation relation in quasi-static mode I dominated delamination of a cross-ply carbon fiber epoxy laminate. The results demonstrate that crack propagation is accompanied by a large bridging zone which is smaller than the zone in a uniaxial composite specimen of the same materials and linear dimensions. While the initiation value of the energy release rate (ERR) is the same, the ERR at steady state propagation and the maximum stress in the bridging zone are respectively 1.7 and 3.1 times larger than the corresponding values of the unidirectional specimen. The obtained traction–separation relation is employed in a cohesive zone model to predict the loading response and crack growth. The adopted approach is a step towards a better understanding of delamination in cross-ply composites.